Resistance response of five maize grain varieties to Sitophilus zeamais and Sitophilus oryzae (Coleoptera: Curculionidae) - Octavianti, Dewi Fortuna; Megasari, Dita; Prasetyawati, Endang Triwahyu (Agrovigor, 2024)
Warehouse pests that have the potential to damage corn kernels are Sitophilus zeamais and Sitophilus oryzae. Information on the resistance of corn kernels of several varieties is still little reported. Research on the resistance response of five varieties of corn kernels (Madura-3, Lokal Madura, Pioneer P32 Singa, P27 Gajah, and NK 212) to S. zeamais and S. oryzae pests was conducted at the Plant Health Laboratory, Agrotechnology Study Program, Faculty of Agriculture, National Development University “Veteran” East Java. This study aims to determine the response of feed type resistance in the form of five varieties of corn seeds to the attack of S. zeamais and S. oryzae pests. The results showed that the highest percentage of mortality of S. zeamais and S. oryzae imago was in corn seeds of Madura-3 (17.15%) and NK 212 (37.22%) varieties. Fecundity tests on S. zeamais and S. oryzae pests with the lowest mean were on corn seeds of P27 Gajah (6.33 grains) and NK 212 (4.33 grains). The lowest percentage of seed weight loss in S. zeamais and S. oryzae pests was in the varieties P27 Gajah (1.34%) and NK 212 (1.05%). The highest percentage of sex ratio of S. zeamais and S. oryzae imago was in the varieties P27 Gajah (1.57%) and NK 212 (1.23%). The conclusion of this study is that the maize seeds that are resistant to S. zeamais attack are the P27 Gajah variety, while the maize seeds that are resistant to S. oryzae attack are the NK 212 variety.